2019
DOI: 10.3389/fncir.2019.00042
|View full text |Cite
|
Sign up to set email alerts
|

Abnormal Interactions of the Salience Network, Central Executive Network, and Default-Mode Network in Patients With Different Cognitive Impairment Loads Caused by Leukoaraiosis

Abstract: Leukoaraiosis (LA) is associated with cognitive impairment in the older people which can be demonstrated in functional connectivity (FC) based on resting-state functional magnetic resonance imaging (rs-fMRI). This study is to explore the FC changes in LA patients with different cognitive status by three network models. Fifty-three patients with LA were divided into three groups: the normal cognition (LA-NC; n = 14, six males), mild cognitive impairment (LA-MCI; n =… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
36
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(42 citation statements)
references
References 24 publications
(37 reference statements)
5
36
1
Order By: Relevance
“…Our findings suggest that the increase in the right posterior parietal cortex might be a compensation effect of the decline in DMN FC. This indicates an antagonistic and complementary relationship between DMN and ECN, which is consistent with the findings of a previous study (44). These findings replicate those of previous studies on patients with AD and, importantly, on patients with aMCI, proving that our experimental design and system were reliable.…”
Section: Findings In Accordance With Previous Studies On Ad and Amcisupporting
confidence: 92%
“…Our findings suggest that the increase in the right posterior parietal cortex might be a compensation effect of the decline in DMN FC. This indicates an antagonistic and complementary relationship between DMN and ECN, which is consistent with the findings of a previous study (44). These findings replicate those of previous studies on patients with AD and, importantly, on patients with aMCI, proving that our experimental design and system were reliable.…”
Section: Findings In Accordance With Previous Studies On Ad and Amcisupporting
confidence: 92%
“…For example, microstructural WM disruption has been documented in ILA, such as the frontal WM tracts and corpus callosum (Yamauchi et al, 2000 ; Jokinen et al, 2007 ; Viana-Baptista et al, 2008 ; Wang et al, 2017 ). Moreover, resting-state functional MRI studies have also shown ILA-related alterations in functional connectivity (Chen et al, 2019 ; Liu et al, 2019a , b ). Therefore, the ILA-related increases in the absolute and normalized path lengths and decreases in the network efficiency might be attributed to disconnections between brain regions.…”
Section: Discussionmentioning
confidence: 99%
“…Diffusion tensor imaging studies on ILA have demonstrated white matter (WM) changes, especially in the fronto-subcortical circuits (Viana-Baptista et al, 2008 ; Yuan et al, 2017 ). Additionally, evidence from functional brain connectome studies on ILA has further shown the involvement of the dysfunction of several networks in ILA, including the default mode network, frontoparietal network, dorsal attention network, salience network and corticostriatal network (Chen et al, 2016 , 2019 ; Liu et al, 2019a , b ). These studies have suggested that “brain network dysfunction” may be the best explanatory model for illuminating the neurobiological pathway underlying cognitive impairment in ILA.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have shown that long-term persistent epileptiform discharges are the cause of cognitive decline in patients with BECTS [3,37]. Recent studies have shown that in patients with a long course of epilepsy, long-term continuous spike discharges will interfere with and reorganize brain functional networks, resulting in the decline of cognitive function [15,38]. Interictal long-term spike discharges may be one of the risk factors for cognitive decline in BECTS.…”
Section: Clinical Datamentioning
confidence: 99%
“…During the resting state, the brain is active in an organized way, and this active network is called the default mode network (DMN), which includes the PCC, the dorsal medial prefrontal cortex (middle frontal gyrus, superior frontal gyrus), dorsal anterior cingulate gyrus, and bilateral angular gyrus [40]. The DMN is thought to be involved in human cognitive function [38,41]. Our study showed that in children with BECTS with cognitive decline, abnormal magnetic source activity was concentrated in the DMN region and was in a state of inactivation compared with healthy children.…”
Section: Source Localizationmentioning
confidence: 99%